Case reportExtra-pulmonary tuberculosis presenting as obstructive jaundice - Mathew, Jomal; Raj, Mithun; Dutta, Tarun Kumar; Badhe, Bhawana Ashok; Sahoo, Ratnakar; Venkatesan, Mukta (Archives of Medical Science, 2007)
Obstructive jaundice as the sole presentation of extra-pulmonary tuberculosis is a rare entity with only a few cases reported in the literature. Patients with this condition usually present with a protracted illness, jaundice and weight loss, which may be confused with hepatobiliary malignancies. A 45-year-old male alcoholic presented with a history of jaundice associated with low-grade intermittent fever and weight loss of one year duration. Diagnostic imaging techniques revealed multiple ill defined nonenhancing lesions in the liver with a 1.0 x 1.0 cm rounded lesion at the porta hepatis and intrahepatic biliary radical dilatation (IHBRD). A provisional diagnosis of Klatskin tumour (cholangio carcinoma involving the confluence of hepatic ducts) with liver secondaries was made. Subsequent histopathology showed caseating granulomatous lymphadenitis with epitheloid granulomas present periportally. He was treated successfully with a four-drug antituberculous regimen with complete resolution of symptoms.